Fieldwork Dynamics in a Higher Education Setting amid the COVID-19 Pandemic - Nyoni, Phefumula; Agbaje, Olaide (Critical Studies in Teaching and Learning, 2023)
This paper highlights how fieldwork, particularly within the context of the COVID-19 pandemic, has undergone changes in response to the pandemic, considering its significance to knowledge production in the academic arena and beyond. The paper presents different fieldwork related circumstances and innovative practices linked to the COVID-19 crisis in aspects such as securing consent from participants, handling the interview process itself, dynamics surrounding interviewer and participant encounters and how they influence validity of data. A group of 8 students from the Humanities faculty and another 8 from the Sciences faculty were purposively chosen with all drawn from the extended programme. Participants also included 8 academics, 4 drawn from each of the two faculties. The implications of one's position, level of reflexivity, and understanding of epistemological assumptions are also explored. The concepts of positionality and reflexivity are used to examine the diverse ways in which the fieldwork process is mediated.